Nutrition‐sensitive lockdowns: Conceptual framework and empirical insights from Africa during COVID‐19. (4th January 2023) - Daum, Thomas; Biesalski, Hans Konrad; Blaschke, Nikola; Bosch, Christine; Güttler, Denise; Heni, Jakob; Kariuki, Juliet; Katusiime, Roseline; Seidel, Anna; Senon, Zinsou‐Narcisse; Woode, George; Birner, Regina
Summary: Motivation: Countries facing challenges of nutrition security confront a trade‐off when dealing with pandemics such as COVID‐19. Implementing lockdown measures, widely used worldwide, can help "flatten the curve" (of disease), but such measures may worsen nutrition security. Purpose: We aim to identify and justify nutrition‐sensitive lockdown measures to reduce trade‐offs with nutrition security. Methods and approach: We propose a conceptual framework which distinguishes eight lockdown measures and six pathways to nutrition security. To demonstrate the relevance of the pathways, we reviewed emerging literature on COVID‐19 and nutrition security. We analysed the content of 1188 newspaper articles on lockdown effects in five African countries: Benin, Ghana, Kenya, Uganda and Zambia. Findings: Some lockdown measures, such as closing workplaces and restricting movement, potentially worsen nutrition far more than others. Banning events and public gatherings have far less impact on nutrition. This can be seen from the framework, the academic literature, and is supported by the analysis of newspaper reports in the five countries. Policy implications: It is better, when possible, to test and trace disease than to lock down. But when lockdowns are needed, the first recourse should be to measures that have few nutritional consequences, such as banning public events. When more drastic measures are necessary, nutritional harm should be mitigated by, for example, exempting farm labour from restrictions on movement, by replacing school meals with take‐home rations, and, above all, providing income support to the most affected and most vulnerable households.